THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL MANAGEMENT, AND MARKET SEGMENTATION ON SALES PERFORMANCE OF CULINARY MSMES FROM THE PERSPECTIVE OF MAQASHID SYARIAH MANAGEMENT - Dery Pratama; Muhammad Kurniawan; Mia Selvina (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to examine the effect of financial literacy, financial management, and market segmentation on increasing sales of culinary SMEs in Bandar Lampung from the perspective of Maqashid Management, which emphasizes the welfare and sustainability of the business holistically. Using a quantitative approach, data were collected through a survey of 110 MSME actors selected by purposive sampling. Data analysis was conducted using the SmartPLS method. Based on the results of the study, explain that financial literacy, financial management, and market segmentation individually and simultaneously have a positive and significant effect on increasing sales of Micro, Small, and medium enterprises (SMEs) in the culinary field in Bandar Lampung. This study also provides policy recommendations for the development of MSEs that are oriented to the values of maqashid Sharia